Reforming Federal Land Management: Cutting the Gordian Knot - Fitzsimmons, Allan K. (Rowman & Littlefield Publishers, 2012)
For over a century, American have created laws, processes, objectives, priorities, and rules for federal land management that often conflict, contradict, and undermine each other. We now find ourselves with inconsistent laws, unclear priorities, procedural mazes, and an antiquated bureaucratic structure. Processes and procedures often impede rather than aid management actions and prevent good stewardship. The overall result is a loss of public benefits and undesirable impact on natural resources. Allan Fitzsimmons presents a clear argument for major changes and offers new ideas for how those changes can be accomplished. Students and professionals interested in public policy, resource management, and environmental studies will find this book to be particularly interesting.